PREVENTING GLOBAL HR ISSUES FOR A BETTER FUTURE FOR THE WORLD - Dr.S.Pandurangan; Dr.S.Sankar (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
Today’s organizations are part of a technologically changing global village. There has been a massive paradigm shift in the way we work, interact and perceive. This pushes HR departments to broaden their horizons to acquire top talent. Strategic management that involves developing and supporting people and creating a positive work environment is known as human resource management. Although their responsibilities vary by organization and industry, they generally include recruitment, compensation and benefits, training and development, and managing employee relations.